2009
DOI: 10.1371/journal.pone.0007471
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutations in GLI3 Lead to Misregulation of its Subcellular Localization

Abstract: BackgroundMutations in the transcription factor GLI3, a downstream target of Sonic Hedgehog (SHH) signaling, are responsible for the development of malformation syndromes such as Greig-cephalopolysyndactyly-syndrome (GCPS), or Pallister-Hall-syndrome (PHS). Mutations that lead to loss of function of the protein and to haploinsufficiency cause GCPS, while truncating mutations that result in constitutive repressor function of GLI3 lead to PHS. As an exception, some point mutations in the C-terminal part of GLI3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 45 publications
(74 reference statements)
2
30
1
Order By: Relevance
“…Transcriptional Activity of GLI3-As we have reported previously, the MID1-␣4-PP2A complex regulates the subcellular localization and transcriptional activity of GLI3 in cancer cell lines (16,17). However, our data also suggested that this regulation indirectly involves other GLI3-interacting proteins.…”
Section: Fu Regulates the Subcellular Localization Andsupporting
confidence: 64%
See 1 more Smart Citation
“…Transcriptional Activity of GLI3-As we have reported previously, the MID1-␣4-PP2A complex regulates the subcellular localization and transcriptional activity of GLI3 in cancer cell lines (16,17). However, our data also suggested that this regulation indirectly involves other GLI3-interacting proteins.…”
Section: Fu Regulates the Subcellular Localization Andsupporting
confidence: 64%
“…As we have shown previously, a protein complex consisting of the microtubule-associated ubiquitin ligase MID1, the ␣4 protein, and protein phosphatase 2A (PP2A) 2 regulates the nuclear localization and transcriptional activity of one of the three transcriptional effector molecules of mammalian SHH signaling, GLI3, in cancer cell lines with autonomously activated SHH signaling (16,17). Via its ubiquitin ligase activity, the RING finger protein MID1 targets PP2A toward ubiquitindependent degradation by the proteasome and thereby decreases PP2A activity at the microtubules (18).…”
Section: Shh (Sonic Hedgehogmentioning
confidence: 95%
“…In vertebrates, PP2A regulates Hh signaling at the level of Gli as well. It has been observed that PP2As regulate the nuclear localization of Gli3 (24,25). We previously reported that B56⑀ positively regulates transcriptional activation function of Gli during Xenopus embryonic development (26).…”
mentioning
confidence: 92%
“…By contrast, haploinsufficiency resulting from chromosomal rearrangements, but also missense, splicing or truncating mutations elsewhere in the gene cause GCPS by loss of the DNA-binding capacity 11 or activation of nonsense-mediated mRNA decay, 12 or by the formation of an unstable or mislocalized protein. 13,14 In this study, we report on the clinical and molecular data of a French cohort of 76 individuals from 55 families carrying a GLI3 molecular defect. Most of mutations are novel and consistent with the previously reported genotype-phenotype correlation.…”
Section: Introductionmentioning
confidence: 99%